The assessing factors of business success among SME Food and Beverages Industry in Kelantan: A pilot study - Yusuf, Yusni Munirah; Ab Rahman, Siti Maziah; Bustaman, Hasnun Anip (International Journal of Accounting, Finance and Business, 2025)
Business success is the achievement of an organization's financial or non-financial goals through effective management, strategic planning, and resource optimization. It encompasses financial, market, social, and personal dimensions. Success is subjective but typically involves sustainable growth, wealth creation, and profitability. According to dynamic capability theory, a robust business strategy involves a firm’s ability to sense and adapt to market changes, with market and demand sensing being critical for understanding consumer needs, predicting shifts, and swiftly capitalizing on new opportunities. This study aims to identify the key factors influencing SME success in F&B sector in Kelantan state, focusing on the relationships on business strategy and its effects on business success, analysed through the dynamic capability theory. Data were collected using purposive sampling from a survey of 30 respondent on well-established SME F&B businesses in Kelantan and analysed using SPSS and PLS-SEM. The results show that through sensing activity and reconfiguring activities could bring business success to the SME. This finding is valuable for F&B entrepreneurs, policymakers, and academics, offering new insights into dynamic capability theory and filling existing research gaps.